The influence of green credit policy on green innovation and transformation and upgradation as a function of corporate diversification: The case of Kazakhstan - Chemirbayeva Mergul Berikhanovna; Bekmukhametova Assemgul Bauirzhanovna; Niyetalina Gaukhar Kudaibergenovna; Bodaukhan Gulbagda; Yerkulova Gulmira Serikovna (Economies, 2023)
This study investigates the heterogeneous effects of the green credit policy (GCP) on firms' green innovation and transformation and upgradation. Using a comprehensive dataset of companies operating in the green sector, we employ panel regression models to examine the interaction between the policy and firm characteristics among SMEs in Kazakhstan. The results reveal significant heterogeneity in the effects of the policy across different scales of enterprises. In terms of green innovation, the policy has a positive and significant impact on large enterprises, while its effects are not significant for small- and medium-sized enterprises. Similarly, for transformation/upgradation, the policy demonstrates a positive effect on large enterprises but lacks significance for smaller firms. These findings suggest that larger enterprises may have a greater capacity and more resources to capitalize on the policy incentives and implement greener practices effectively. Additionally, the study identifies technological capability as a mediating factor and regulatory environment as a moderating factor influencing the relationship between the policy and green outcomes. The theoretical implications highlight the importance of considering firm characteristics and contextual factors in understanding the heterogeneous effects of environmental policies. From a practical standpoint, policymakers should tailor policy interventions to account for the varying needs and capacities of different scales of enterprises. Moreover, fostering technological capability and improving the regulatory environment can enhance the effectiveness of green policies.
Keywords: 330; green credit policy; green innovation; heterogeneous effects; technological capability; transformation and upgradation